Regulation of susceptibility and cell surface receptor for the B-lymphotropic papovavirus by N glycosylation. - Keppler, O T (1994)
The host range of the B-lymphotropic papovavirus (LPV) in cultured human cells is limited to a few B-lymphoma-derived cell lines. The constitutively expressed cell surface receptor for the virus is a major determinant restricting the LPV host range (G. Haun, O. T. Keppler, C. T. Bock, M. Herrmann, H. Zentgraf, and M. Pawlita, J. Virol. 67:7482-7492, 1993). Here we show that human B-lymphoma cells with low-level susceptibility are rendered highly susceptible to LPV infection by pretreatment with the N glycosylation inhibitor tunicamycin but remain nonsusceptible to infection by the related polyomavirus simian virus 40. Among the selective N glycosylation processing inhibitors, deoxymannojirimycin, but not deoxynojirimycin, swainsonine, or castanospermine, could mimic the effect of tunicamycin. Tunicamycin treatment also induced a drastic enhancement of the cells' LPV-binding capacity, indicating that the induction of LPV susceptibility might be mediated by an increase in the number of functional cell surface receptors and/or by increased receptor affinity. Sialidase sensitivity of the tunicamycin-induced LPV receptor showed that oligosaccharides carrying terminal sialic acids are necessary for binding and are likely to be O linked. The constitutive LPV receptor is also sialic acid dependent, which points to a possible identity with the sialic acid-dependent tunicamycin-induced LPV receptor. We conclude that removal or modification of certain N-linked oligosaccharides in human B-lymphoma cells can enhance expression or functional activity of the sialylated LPV receptor.